Karakteristik Ibu Hamil dengan Insidensi Plasenta Previa pada Ibu Hamil di RSU HKBP Balige Kabupaten Toba - Sifra Sopia Sinaga; Marta Armita Silaban (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Background: According to data from the World Health Organization (WHO, 2023), antepartum hemorrhage, especially placenta previa, accounts for 15% to 20% of maternal deaths. Placenta In addition, previa accounts for 3% of all maternal deaths in Indonesia due to bleeding. Abnormal implantation of placental tissue above the endocervical os is a characteristic of placenta previa. Parity, age, endometrial hypoplasia, tumors, slow luteal response, endometrial abnormalities, history of cesarean section, curettage, multiple pregnancies, and history of placenta previa in previous pregnancies are some of the factors that can increase the risk of placenta previa. Research Objective: This is to determine the characteristics of pregnant women with the incidence of placenta previa in pregnant women at the HKBP Balige Hospital in 2024. Research Method: This is analytical with a cross-sectional design. The sampling technique uses total sampling with a sample size of 45 people. The entire data processing and analysis process uses the SPSS application. Research Results: The characteristics of pregnant women were obtained as follows: the majority of the age at risk (<20 and >35 years) as much as 55.6%; the majority of parity >3 as much as 53.3%, the majority of Ever CS as much as 60%. Results: statistical tests showed a significant correlation with the characteristics of pregnant women with age (p = 0.007), parity (p = 0.031) and history of CS (p = 0.001). Suggestion: It is expected to facilitate health workers in increasing knowledge and skills through training in maternal and neonatal emergency services as an effort to prevent complications in the mother and fetus.